Candida antarctica B lipase-catalysed alcoholysis of peracetylated alkyl D-ribofuranosides - Gudiño, Esteban Dario; Iribarren, Adolfo Marcelo; Iglesias, Luis Emilio (Biocatalysis and Biotransformation)
Candida antarctica B lipase (CAL-B) catalysed alcoholysis of a series of peracetylated alkyl α, β-D-ribofuranosides was assayed. Methyl and ethyl 2,3-di-O-acetyl-α, β-D-ribofuranosides enriched in the α-anomer were regioselectively prepared through this enzymatic deacetylation in 33% and 43% yield, respectively, the latter being a new compound. Isopropyl 2,3,5-tri-O-acetyl-β-D-ribofuranoside gave the new isopropyl 2,3-di-O-acetyl-β-D-ribofuranoside in 24% yield. The anomeric substituent affects the regioselectivity of the reaction, since n-propyl and n-butyl α, β-D-ribofuranosides reacted without selectivity. Fil: Gudiño, Esteban Dario. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Iribarren, Adolfo Marcelo. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones en Ingeniería Genética y Biología Molecular "Dr. Héctor N. Torres"; Argentina Fil: Iglesias, Luis Emilio. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina